Effect of Cross-flow Velocity and Temperature in Microfiltration of Wax Apple (Syzygium samarangense) Juice - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2020)
Wax apple (Syzygium samarangense) fruit has a good source phenolics, flavonoids and antioxidant constituents with great potential benefits for human health. Its pulp is crisp and watery, slightly acid flavor to a full and fruity apple flavour. Microfiltration is an emerging technology, a good alternative for the fruit juice processing with a significant interaction to sensory and nutritional attributes. Purpose of our research verified the feasibility of different variables of cross-flow velocity (3.2, 4.0, 4.8, 5.6, 6.4 m/s) and temperature (22, 26, 30, 34, 38oC) in microfiltration using hollow fibre membrane to permeate flux (L/m2h), total phenolic (mg GAE/g) and flavonoid (mg GE/g) in wax apple juice. Our results revealed that the microfiltration should be performed at cross-flow velocity 4.8 m/s at temperature 34oC to get the highest permeate flux, total phenolic and flavonoid.Keywords: Wax apple juice, Microfiltration, Cross-flow velocity, Temperature, Permeate flux, Total phenolic, Flavonoid.